FOREIGN VESSEL SINKING POLICY IN ERADICATING ILLEGAL, UNREPORTED, AND UNREGULATED (IUU) FISHING IN THE INDONESIAN EXCLUSIVE ECONOMIC ZONE (IEEZ) - Richard Al Khalik; Nellyana Roesa (Student Journal of International Law, 2022)
The relevance of foreign vessel sinking policy to eradicate IUU fishing in IEEZ by national regulation to UNCLOS 1982 is questionable. This paper uses a normative legal analysis,  examining international conventions and national regulation provisions and their application to legal events. The results indicate that implementing the foreign vessel sinking policy is national law enforcement of  Law No. 45 of 2009 amendment to the  Law No. 31 of 2004 Concerning Fishery,  Article 69 (1) and (4). The foreign vessel sinking policy is not contrary to UNCLOS 1982 because the subject protected in EEZ by Article 73 (3) is the human being, not the vessel. It remains an effective means to create a deterrent effect as an optimum penalty for such crime.